Swimming Upstream : Hédi Bouraoui’s En Amont de l'intuition - Sabiston, Elizabeth (Revue CMC Review, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Hédi Bouraoui’s recent collection, En Amont de l’Intuition (Toronto: CMC Éditions, 2013), is a pithy, pungent, short group of poems suggested by the notion of “Intuition” and “Intuitist” poetics. A bilingual collection (French/ Italian) with Italian translations by Mario Selvaggio and illustrations by a number of contemporary artists, the poems were originally published in Au-delà de l’instant: Anthologie des poètes intuitistes, edited by Giovanni Dotoli, Mario Selvaggio, and Éric Sivry (Fasano, Italy: Schena Editore, 2012). Bouraoui’s take on the subject of “Intuition” is critical, and often ironic. “Intuition”is a free-floating, amorphous source of poetry which, by definition, is impossible to define. Without sticking pins in the butterfly, Bouraoui’s project is to delimit the parameters of the impulse to poetry. His title itself ironizes that of the Dotoli-Selvaggio-Sivry text (Äu-delà de l’instant…) into En Amont de l’Intuition, which means above intuition, not “beyond,” but which also implies swimming upstream, like the salmon, or struggling against the tide. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->